PADI4 Polymorphisms Confer Risk of Anti-CCP-Positive Rheumatoid Arthritis in Synergy With HLA-DRB1*04 and Smoking - Massarenti, Laura; Enevold, Christian; Damgaard, Dres; Ødum, Niels; Garred, Peter; Frisch, Morten; Shelef, Miriam A.; Jacobsen, Søren; Nielsen, Claus Henrik (Frontiers in Immunology, 2021)
Peptidylarginine deiminases (PADs) catalyze citrullination, a post-translational modification playing a pathogenic role in anti-citrullinated protein antibody (ACPA)-positive rheumatoid arthritis (RA). The interplay between single nucleotide polymorphisms (SNPs) in the PADI genes and known risk factors for ACPA-positive RA, including smoking, HLA-DR4 and -1, and the PTPN22 R620W polymorphism was investigated. We typed four PADI2 SNPs, four PADI4 SNPs and the PTPN22 R620W SNP in 445 Danish RA patients and 533 age-matched healthy controls as well as in 200 North American RA patients and 100 age- and sex-matched controls. The HLA-DRB1 locus was typed in the Danish cohort. Logistic regression analyses, adjusted for age, sex, smoking status and PTPN22 R620W, revealed increased risk of anti-CCP-positive RA in carriers of rs11203367(T) (OR: 1.22, p=0.03) and reduced risk in carriers of rs2240335(A) in PADI4 (OR: 0.82, p=0.04). rs74058715(T) in PADI4 conferred reduced risk of anti-CCP-negative RA (OR: 0.38, p=0.003). In HLA-DRB1*04-positive individuals, specifically, the risk of anti-CCP-positive RA was increased by carriage of PADI4 rs1748033(T) (OR: 1.54, p=0.007) and decreased by carriage of PADI4 rs74058715(T)(OR: 0.44, p=0.01), and we observed an interaction between these SNPs and HLA-DRB1*04 (p=0.004 and p=0.008, respectively) Thus, PADI4 polymorphisms associate with ACPA-positive RA, particularly in HLA-DRB1*04-positive individuals, and with ACPA-negative RA independently of HLA-DRB1*04.